Knowledge of resilience strategies in livestock management during dry periods in southwestern Nigeria - Fadairo, Anjolaoluwa O.; Popoola, Yemi A.; Sorunke, Adekunle O.; Omole, Adeboye J. (International Journal of Environment, 2023)
Recurring elongated dry seasons in South west Nigeria pose a significant threat to livestock production. Knowledge of adaptation strategies to build resilience and lowers vulnerabilities to climate change among livestock farmers is limited. This study assessed livestock farmers’ knowledge of resilience strategies in farm management during dry seasons in southwest Nigeria. Using a purposive sampling procedure, a total of 118 farmers were interviewed on knowledge of livestock management during dry periods, specific challenges to management, and opinions on efficient livestock management. The result shows that increased feed costs challenged farmers during the dry season while insufficient funds were identified as the most severe constraint. Knowledge of management was high among 42% of farmers and 89.5% of them disagreed on the mechanism for temperature control structure in livestock building. Knowledge of good management practices was influenced by farmers’ ability to read and write in Yoruba language (χ2= 9.179; p < 0.05) and constraints faced (r = 0.21; p < 0.05). Climate change information in local languages will improve livestock farmers’ resilience to challenges induced by unpredictable climate change.